Novel stable structure of Li3PS4 predicted by evolutionary algorithm under high-pressure - S. Iikubo; K. Shimoyama; S. Kawano; M. Fujii; K. Yamamoto; M. Matsushita; T. Shinmei; Y. Higo; H. Ohtani (AIP Advances, 2018)
By combining theoretical predictions and in-situ X-ray diffraction under high pressure, we found a novel stable crystal structure of Li3PS4 under high pressures. At ambient pressure, Li3PS4 shows successive structural transitions from γ-type to β-type and from β-type to α type with increasing temperature, as is well established. In this study, an evolutionary algorithm successfully predicted the γ-type crystal structure at ambient pressure and further predicted a possible stable δ-type crystal structures under high pressure. The stability of the obtained structures is examined in terms of both static and dynamic stability by first-principles calculations. In situ X-ray diffraction using a synchrotron radiation revealed that the high-pressure phase is the predicted δ-Li3PS4 phase.